Quality of seeds of Pinus koraiensis Siebold et Zucc. (Pinaceae) in Ukrainian plantations - О.P. Pokhylchenko (Інтродукція Рослин, 2015)
The area of Pinus koraiensis Siebold et Zucc. (Korean pine) decreases, so many trees are protected. In world practice there are example of successful cultivation of edible seeds of pine. Several plantations were created in Ukraine. The size and weight of seeds collected in 2012 and 2013 years in different regions of Ukraine correspond to the same indicators in natural growth. On the plantations with the best pollination mode, 21–30 % of ovules die not fertilized (40 % for the plantations with fewer trees) during crop years; the figure for lean years is 98 %. From 2.4 to 59.0 % of pollinated ovules die during fertilization; from 2 to 89 % of them die from the effects of uncertain biotic factors. On the plantations with the most favorable pollen conditions, 107–130 seed buds of each pollinated cones successfully pass the fertilization phase; 87–95 % of them are full of seeds capable to germinate.